This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A s x + y = 1 7 . . . . . . . . . . . . . . . . ( i ) x 2 + y 2 = 1 6 7 . . . . . . . . . . . . ( i i ) T a k i n g S q u r e o f ( i ) , w e h a v e = > ( x 2 + y 2 ) + 2 x y = 2 8 9 = > ( 1 6 7 ) + 2 x y = 2 8 9 ∵ x 2 + y 2 = 1 6 7 = > 2 x y = 2 8 9 − 1 6 7 = > 2 x y = 1 2 2 = > x y = 2 1 2 2 S o , x y = 6 1
x+y=17 x^2+y^2+2xy=289 2xy=289-167 xy=61
Problem Loading...
Note Loading...
Set Loading...
I will derived my own identity.
( x + y ) 2 − 2 x y = x 2 + 2 x y + y 2 − 2 x y = x 2 + y 2 .
Now just plug in the given quantities in the derived formula. We have
1 7 2 − 2 x y = 1 6 7
2 x y = 1 7 2 − 1 6 7 = 1 2 2
Finally,
x y = 6 1